TEACHING YOUNG ADULT LITERATURE: CATCHER IN THE RYE AS A LANGUAGE MAKER AND BREAKER - Ayan, Meryem (PEOPLE: International Journal of Social Sciences, 2017)
Young adult literature dealing with familiar universal youth problems and concerns that most of young adults either have experienced or are still experiencing has many qualities which make it particularly suitable for English literature lecturers and foreign language instructors to use it in their curriculums. Young adult literature enables young adults to identify themselves with the familiar youth problems during the maturational and experiential development period and serves as a great motivator for teaching language and developing reading skills. Namely, young adult literature as a developing genre is a valid pathway to engage young adults in learning language through reading literary texts. However, when first published, The Catcher in the Rye (1951) as a young adult literature was banned from schools because of portraying a 17-year-old young adolescent using obscene and offensive language. In fact, the language seen as obscene and offensive and inappropriate in adult worlds is very appropriate in the young adult worlds because it is true to their colloquial speech. Thus, aiming to present young adult literature and its usage in teaching language and improving reading, Salinger's novel will be analyzed with reader response approach, discussing whether teaching young adult literature: The Catcher in the Rye is a language maker or breaker.